Tuberculosis in patientes treated with tumor necrosis factor-alpha antagonists living in an endemic area. Is the risk worthwhile? (2007)
Tumor necrosis factor alpha antagonists (TNFA) are biological agents to treat chronic inflammatory and autoimmune diseases. However, their use is associated with an increased rate of tuberculosis, endemic mycoses, and intracellular bacterial infections. Since tuberculosis is moderately to highly endemic in Colombia, the risk of these infections in patients treated with TNFAs may be higher than previously reported in Colombia. Recently, four patients have developed tuberculosis during TNFA therapy. Tuberculosis appeared between 3 to 24 months after initiation of TFNA therapy and was independent of previous tuberculin skin test status. A review of the relevant literature and recommendations are presented as guides for surveillance and prophylaxis on a country-wide basis.